2007
DOI: 10.1051/0004-6361:20066938
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a system with cosmic rays and waves

Abstract: Aims. We investigate the the stability of a cosmic-ray plasma system using the hydrodynamic approach. Methods. The system we are considering comprises cosmic rays and two oppositely propagating Alfvén waves. The thermal plasma flow is treated as a background, such that the feedback of the cosmic rays and waves is neglected. Steady-state solutions exist for the system, and when two waves are present, the steady state is non-uniform. Linear stability analysis on the steady-state solutions shows that for short wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The downstream regions of the quasi-uniform-flowtype solution are stable. This is consistent with the result of Lo & Ko (2007), which considered a system with a prescribed uniform flow. In contrast, the downstream regions of the modified-shocktype solution are unstable.…”
Section: An Examplesupporting
confidence: 91%
See 4 more Smart Citations
“…The downstream regions of the quasi-uniform-flowtype solution are stable. This is consistent with the result of Lo & Ko (2007), which considered a system with a prescribed uniform flow. In contrast, the downstream regions of the modified-shocktype solution are unstable.…”
Section: An Examplesupporting
confidence: 91%
“…In the reduced system where the background plasma flow is not perturbed, Lo & Ko (2007) found that the instability is due to stochastic acceleration. Since stochastic acceleration is absent in unidirectional wave systems, we might expect that they should be less susceptible to the instability than the twowave systems.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations